(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The objective of the study is to explore the structure and dynamics of medium-sized cities in Peru for the period of 2007 and 2017. The results show a high urban primacy and the resurgence of national urban growth; on an important demographic presence of medium-sized cities and it was a period of greater dynamism of small towns in 2017 and intermediate ones in 2007. Thus, the population of medium-sized cities settled mainly in the coastal region, while they had higher growth those located in the mountains. Medium-sized cities are found mainly in the northern and central Macroregions, but those in the south were dynamic. Spatial factors had little relevance in the dynamics of medium-sized cities, except for density. It is found that poverty is directly related to the size of medium-sized cities; and the poverty levels of the medium-sized cities were lower in the Southern Macroregión.